Ensuring Good Governance in Rwanda: Is this Experience Transferable to EAC Countries? - Kamila, Dwi Warda Cahya (Faculty of Social and Political Sciences, UIN Sunan Ampel Surabaya, 2024)
The Rwandan Patriotic Front (RPF) played a key role in the implementation of good governance in Rwanda after the 1994 genocide. Rwanda managed to restore stability and rebuild the country through structural reforms driven by RPF initiatives. UNDP contributed by building the capacity of government institutions, supporting judicial reform through Gacaca Courts, and advancing social and economic capacity through the Girinka and Mutuelle de Santé programs. The Vision 2020 initiative launched by the RPF focuses on economic transformation through infrastructure development and private sector empowerment, while Mutuelle de Santé expands access to health services, and Girinka aims to improve the economic and nutritional well-being of the community. In addition, the Umuganda program is one of the ways Rwanda can keep nature clean, and also the ban on using plastic bags can be a step in protecting the environment. These programs, along with Good Governance concept support, have strengthened transparency, accountability, and social reconciliation in Rwanda. The good governance model implemented in Rwanda, including economic reform, health access, and poverty alleviation, shows potential for implementation in EAC countries, although adaptation challenges must be considered